EFFECTIVE HIGHER SCHOOL MANAGEMENT - CICHOŃ, Seweryn (Trends in education, 2013)
Higher education management is directing of the actions realized by particular organizational units of the school or people at certain levels of an organizational structure. The duty of a manager of a higher school, a faculty or another unit is the elimination of the all causes that bring negative results in a decisive process and are conducive to the growth of the work quality, and especially to the management quality. Creating and stimulating the demand for educational services by the authorities have become a standard. Such school areas as work organization, improving of educational services quality, education attractiveness and marketing actions still need a constant development in order to function in the service market.
Keywords: human resources; management; educational services market